Supplementary Biscuits for the Recovery of Malnourished Children in Indonesia - Setyawati, Budi; Fuada, Noviati; Nazarina; Rachmawati, Rika; Salimar; Ernita (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2023)
The objective of this research was to study the nutritional status of children before receiving biscuits, the biscuit supplementation regularity, the adequacy of the biscuits received and consumed by the children according to recommendations, and the relationship between supplementary biscuits consumption and nutritional status. Using a cross-sectional study design, the study was conducted in 2017 involving 586 children in three regions (11 provinces) in Indonesia. A chi-square test was performed to see the relationship between supplementary biscuits consumption and nutritional status. The most common nutritional problems were stunting-wasting (34.1%), stunting (32.6%), and wasting (23.9%). The nutritional problems occurred most often in the eastern region (96.4%), followed by the central region (95.5%) and the western (87.1%). Within three months, 66–78% of respondents received supplementary biscuits regularly, but only 10–29% received the supplementary biscuits as recommended in the same period. Within the three months’ period, from respondents that received the supplementary biscuits as recommended, the region in which children consumed the biscuits according to the recommendations the most was the eastern region (45.2%), followed by the western (23.3%) and central regions (5.3%). Children who consumed biscuits as recommended in the three months’ period had a 2.9 times possibility of having a normal nutritional status (categorized based on the weight-for-age index) (p-value=0.049).